Trajetórias: os rumos do jornalismo contemporâneo - Sousa, Maria Gabriela Barros de (2023)
With technological development and economic changes resulting from capitalism, society has undergone significant changes. Many professions were extinct and others were irrevocably transformed. Journalism was one of the categories that underwent the most changes to the detriment of the phenomena of precariousness and platformization. This magazine takes a sensitive and in-depth look at these conditions and tries to profile the journalists present in the current job market in the state of Ceará and Brazil. The main problems of this research are to understand the functions of a journalist in the current job market, as well as the differences between journalism and press relations, in addition to the relationship between journalism and social networks and the impact of precariousness on daily life. day of communication professionals. To develop this magazine, I read several academic texts, including scientific articles, books and coursework with convergent themes, and interviewed several people who work in journalism and consultancy. I spoke with writers, photographers, art directors, producers, screenwriters, social media, university professors and union leaders in order to provide a realistic experience for readers of this product. In this sense, I believe that my biggest personal gain from carrying out this course completion work was the even deeper knowledge about my profession, the good and bad things of being a Brazilian journalist. In addition to understanding the social importance of journalists, as the media can directly contribute to the well-being of all citizens if they act ethically and responsibly.